Alveolar macrophages and type I IFN in airway homeostasis and immunity. Issue 5 (May 2015) - Divangahi, Maziar; King, Irah L.; Pernet, Erwan
Highlights The airways are constantly patrolled by alveolar macrophages. Alveolar macrophages are indispensable for tissue homeostasis and host defense. Alveolar macrophages are the major source of type I IFN following immune challenge. Type I IFNs regulate antimicrobial and inflammatory responses of pulmonary macrophages. Eicosanoids modulate type I IFN signaling and production following pathogen invasion.